Rethinking Vocational Rehabilitation through Institutional Ethnography (Journal of Comparative Social Work, 2017)
In Norway, vocational rehabilitation for people with support needs involves complex inter-professional and inter-organizational processes that do not have clear institutional boundaries. Every process involves a new constellation of actors, representing divergent practices, ideas and objectives. This article argues that much of the current research on the implementation of activation policy inadequately captures the mechanisms and processes that influence vocational rehabilitation practices. The article proposes the use of institutional ethnography (IE) to empirically examine vocational rehabilitation, and argues that IE provides methodological concepts and tools that enable researchers to link and make visible the everyday practices, the social relations and the institutional contexts that make up vocational rehabilitation processes.